Tackle characteristics and outcomes in match-play rugby league: The relationship with tackle ability and physical qualities - Speranza, M. J. A.; Gabbett, T. J.; Greene, D. A.; Johnston, R. D.; Townshend, A. D. (Science and Medicine in Football, 2017)
Purpose: This study examined tackle characteristics and their relationships with match-play tackle outcomes, tackling ability, and physical qualities in rugby league players. Methods: Fifteen rugby league matches were analysed, with the tackle characteristics and outcomes of 2355 tackle events coded. Muscle strength and power tests, and a standardized assessment of tackling ability were performed in 16 players. Results: Medium body position, utilizing a shoulder or smother tackles, and producing leg drive upon contact decreased the odds of a missed tackle. Performing a front-on tackle, with a contact zone at the chest region reduced the odds of an offload. Tackling ability was significantly related to defenders moving forward prior to contact (rs = 0.60, 95% CI 0.15-0.85, P = 0.02), front-on tackles (rs = 0.53, 95% CI 0.05-0.81, P = 0.04), and displaying medium body height (rs = 0.57, 95% CI 0.10-0.83, P = 0.02) in match-play tackles. Lower-body strength was significantly related to defenders exhibiting a medium body position (rs = 0.60, 95% CI 0.15-0.85, P = 0.01) and the ball-carrier being placed on their back (rs = 0.72, 95% CI 0.35-0.90, P = 0.002). Conclusion: The findings suggest that match-play tackle performance is related to both tackle characteristics and physical qualities.